Josip Jelačić - Ban of Croatia - Čuvalo, Ante (Array, 2008)
Summary: Author marked the 160th anniversary of the 1848 revolution in which Ban Jelačić played a significant role. Jelačić has been attacked from many sides, as a Panslavist, as a pro Russian, as an Austrophile, and as reactionary. Even after his death, he was a hero to some and a villain to others. To Croats he became a symbol of the struggle against the Magyars, martyred by a devious Austrian regime. Consequently, they erected a monument in his honor in Zagreb’s main square and they composed patriotic songs about him that carried his name to subsequent generations. But after World War II he was condemned once more – this time by the communists – as an antirevolutionary, reactionary figure. His monument was removed from public view and songs commemorating his service were banned. The collapse of the communist regime coincided with returned of Jelačić’s monument to the main square in Zagreb, which now also bears his name